Muckraker websites (American and European examples) - Adamczyk, Wojciech (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The goal of the article is to compare contemporary websites used by investigative reporters for organising their inquiries and propagating their outcomes. To achieve that goal, I compare the experiences of American and European muckrakers in conducting investigative activities through websites. I analysed 10 such projects in total, 3 from the USA and 7 from Europe. The discussed criteria include the modes of financing, the size of annual budgets, the modes of operation, and HR policies.